Analisis Pengaruh Kualitas Aplikasi Free Fire Di Jayapura Menggunakan Metode Servqual - putra, Fiqram; Emy L. Tatuhey (CV Edujavare Publishing, 2025)
The rapid development of digital technology has driven the growth of the online gaming industry in Indonesia, including in eastern regions such as Jayapura. One of the most popular games is Free Fire, which offers various attractive features and is accessible to a wide audience. However, in the highly competitive gaming industry, the quality of application services is a crucial factor in maintaining user loyalty. This study aims to analyze the service quality of the Free Fire application in Jayapura using the SERVQUAL method, which measures five service dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The research involved 35 active Free Fire users in Jayapura, using a questionnaire consisting of expectation and perception components. Data were analyzed using SPSS for validity testing, reliability testing, and GAP (P–E) analysis. The results show that all dimensions have positive GAP values, indicating that user perceptions exceed their expectations. The Responsiveness dimension recorded the highest GAP (0.50), followed by Reliability (0.46), Assurance (0.24), Empathy (0.17), and Tangibles (0.05). These findings indicate that the Free Fire application has successfully delivered satisfying services to users in Jayapura. This study recommends that developers maintain strong service dimensions and improve those with relatively lower GAP scores to optimize overall service quality.